(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: Bullying is a continuous and deliberate abuse of a child or adolescent by another. It is a global problem, and it usually goes undetected during the pediatric practice. Objective: to develop and describe a global bullying index in children and adolescents aged 9-11 years hospitalized or assisted at a public and at a private health institution in Montevideo. Materials and methods: cross-sectional study. Children from 9 to 11 years of age, from Montevideo, hospitalized or assisted at a public and at a private health institution during July to September 2017. Variables: sex, age, health provider, school performance, school center, use of psychotropic drugs, body mass index. The Cisneros Autotest described the Global Bullying Index and the Bullying Intensity. The methods were approved by the Ethics Committees of both participating health institutions. Results: 83 children participated in the study: 52% girls; 34% 9 years old, 38% 10 years old, 28% 11 years old; 54% from private health provider, 88% from public education system. 59% had good school performance; overweight 18%, obesity 16%; use of psychoactive drugs 16%. The global bullying rate was low 51%, high 38%. We found a link between high risk of bullying and type of school, use of psychotropic drugs and psychosocial admission diagnosis. Intensity was high in 73%. The most common type of bullying described was “social exclusion” and “verbal harassment”. Conclusions: we found high-risk of bullying, and found that its intensity and modality have become increasingly concerning.